Inspiring rural youth to consider healthcare careers through an interprofessional healthcare traveling roadshow - Mytting, Kristjan; Muermann, Martin; Maurice, Sean B. (Frontiers in Public Health, 2024)
There areis a well-documented shortages of healthcare providers in rural and remote communities throughout Canadaworldwide, and these shortages correlate with inequitable health outcomes for rural peoples. Despite a wide array of efforts to remedy the issue, theseis shortages persists to this day. The Healthcare Travelling Roadshow (HCTRS) is a grassroots initiative that began in 2010 to help address the shortage of healthcare providers in rural communities throughout British Columbia. Since its inception, the HCTRS has been predicated on three evidence-based guiding principles which have been shown to markedly increase the rate at which healthcare students choose to practice rurally. These principles are: 1) to showcase healthcare careers as viable and realistic options for rural youth (high school students) using interactive stations and near-peer teaching; 2) to expose healthcare students to rural communities and showcase them as a potential opportunity for their future practice; and 3) to provide a unique interprofessional experience to healthcare students from diverse healthcare careers and backgrounds. Through the synergy of these three principles the HCTRS aims to increase the longitudinal recruitment and retention of healthcare workers in underserved rural communities. This paper will share our experience from 15 years of running this initiative, for those hoping to implement similar programs in other areas of the world.